The novel transcriptional factor HP1BP3 negatively regulates Hsp70 transcription in Crassostrea hongkongensis - Delin Xu (Nature Portfolio, 2017)
Abstract ChHP1BP3, a chromatin complex-related protein known with dynamic features, was identified as a ChHsp70 promoter-associated factor in Crassostrea hongkongensis by DNA-affinity purification and mass spectrometry analysis. Direct interaction between purified ChHP1BP3 and the ChHsp70 promoter region was demonstrated using EMSA. ChHp1bp3 depletion led to clear enhancements in ChHsp70 mRNA expression in C. hongkongensis hemocytes. However, ChHp1bp3 overexpression in heterologous HEK293T cells correlated with fluctuations in ChHsp70 transcription. Quantitative RT-PCR analysis showed that both ChHsp70 and ChHp1bp3 transcription were responsive to external physical/chemical stresses by heat, CdCl2 and NP. This indicated a plausible correlation between ChHsp70 and ChHp1bp3 in the stress-induced genetic regulatory pathway. While, the distinctive ChHp1bp3 expression patterns upon physical and chemical stresses suggest that the mechanisms that mediate ChHp1bp3 induction might be stress-specific. This study discovered a novel role for HP1BP3 as a negative regulator in controlling Hsp70 transcription in C. hongkongensis, and contributed to better understanding the complex regulatory mechanisms governing Hsp70 transcription.